2022
DOI: 10.1093/femsle/fnac004
|View full text |Cite
|
Sign up to set email alerts
|

Clonal relationship between multidrug-resistant Escherichia coli ST69 from poultry and humans in Lusaka, Zambia

Abstract: Multidrug-resistant (MDR) Escherichia coli in food animals such as chickens is an emerging public health concern in Zambia. Additionally, the country's high demand for poultry products necessitates further investigation into the link between poultry and human MDR E. coli. Twenty cefotaxime-resistant E. coli isolates collected from poultry in Lusaka, Zambia, were screened for multidrug resistance and sequenced on MiSeq and MinION platforms. Genomes were assembled de novo and compared to 36 previously reported c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 0 publications
5
12
2
Order By: Relevance
“…This correlates with a previous publication that reported potential clonal transmission between the two reservoirs (humans and poultry) in a rural Ghanaian town [30]. Another recent African study, which also correlates with results from the present study, showed a complex relationship between multi-resistant E. coli isolates in poultry and humans indicating that multi-resistance control must involve a One-Health approach and a multi-sectoral collaboration [32]. In our study, the isolation of closely related E. coli ST1722 isolates from humans that were not in close proximity to each other furthermore indicates clonal spread of resistant bacteria in the human community.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This correlates with a previous publication that reported potential clonal transmission between the two reservoirs (humans and poultry) in a rural Ghanaian town [30]. Another recent African study, which also correlates with results from the present study, showed a complex relationship between multi-resistant E. coli isolates in poultry and humans indicating that multi-resistance control must involve a One-Health approach and a multi-sectoral collaboration [32]. In our study, the isolation of closely related E. coli ST1722 isolates from humans that were not in close proximity to each other furthermore indicates clonal spread of resistant bacteria in the human community.…”
Section: Discussionsupporting
confidence: 93%
“…Another recent African study, which also correlates with results from the present study, showed a complex relationship between multi-resistant E. coli isolates in poultry and humans indicating that multi-resistance control must involve a One-Health approach and a multi-sectoral collaboration [32]. In our study, the isolation of closely related E.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The other STs: ST10, ST69, ST58 and ST1308 have previously been isolated from both humans and livestock (Borges et al, 2019;Day et al, 2019;McKinnon et al, 2018;Seo et al, 2023;Shawa et al, 2021). ST10, ST58, and ST69 are commonly associated with extraintestinal infections in humans (Manges et al, 2019;Riley, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…ST131 is the predominant lineage associated with ESBL-associated human urinary tract and blood infections globally [56,57], although other lineages such as ST69 are on the rise [56,58]. Both ST131 and ST69 strains have been isolated from other animals, particularly poultry and dogs, worldwide [27,[59][60][61].…”
Section: Genetic Relatednessmentioning
confidence: 99%